Peran Etika Dan Profesi Kependidikan Dalam Membangun Karakter Peserta Didik Dan Mahasiwa Calon Guru SD - Gibran Andika Pratama; Henry Aditia Rigianti (Universitas Muhammadiyah Kuningan, 2023)
This research is motivated by the characteristics of prospective elementary school teacher students who must be built to mentally prepare them, so that they become prospective elementary school teachers who have noble character and are in accordance with the demands of the ages. In this case the effort that must be made to build the character of students majoring in PGSD is by placing lectures on Professional and Educational Ethics so that they become a forum for providing character education for students majoring in PGSD. Professional teachers are also not only teachers who rely solely on material, but must also rely on their moral qualities and must also uphold the values ​​of the professional code of ethics. This research will also discuss several studies, which include: Ethics and Profession Building character for prospective teachers, instilling character values ​​in the Course of Professional and Educational Ethics, Compilation of Lecture Guidelines for Professional and Educational Ethics by instilling character values, Role Ethics and Profession in instilling the character and skills of prospective elementary school teacher students, integrity in the Professional and Educational Ethics Course in building the character of prospective elementary school teacher students, Evaluation of the Process of Applying the Professional and Educational Ethics Course.